A Combination of Human Embryonic Stem Cell-Derived Pancreatic Endoderm Transplant with LDHA-Repressing miRNA Can Attenuate High-Fat Diet Induced Type II Diabetes in Mice - Yunya Chen; Xiujie Wang; Xinyu Shao (Journal of Diabetes Research)
Type II diabetes mellitus (T2D) is a chronic metabolic disorder that results from defects in both insulin secretion and insulin action. The deficit and dysfunction of insulin secreting β-cell are signature symptom for T2D. Additionally, in pancreatic β-cell, a small group of genes which are abundantly expressed in most other tissues are highly selectively repressed. Lactate dehydrogenase A (LDHA) is one of such genes. Upregulation of LDHA is found in both human T2D and rodent T2D models. In this study, we identified a LDHA-suppressing microRNA (hsa-miR-590-3p) and used it together with human embryonic stem cell (hESC) derived pancreatic endoderm (PE) transplantation into a high-fat diet induced T2D mouse model. The procedure significantly improved glucose metabolism and other symptoms of T2D. Our findings support the potential T2D treatment using the combination of microRNA and hESC-differentiated PE cells.